Deciduous Fruit for the Home Garden in Central Florida - T. E. Crocker; A. J. Rose; Jeffrey G. Williamson; Peter C. Andersen (EDIS, 2009)
Revised! Circular 1221, an 18-page illustrated circular by T. E. Crocker, A. J. Rose, J. G. Williamson, and P. C. Andersen, describes the various types of orchard fruits, their suitability to the Florida home orchard, and the process involved in raising a home orchard. Includes references. Published by the UF Department of Horticultural Sciences, May 2009.